KUALITAS AUDIT DAN FAKTOR YANG MEMPENGARUHINYA: PERSPEKTIF AUDITOR DAN PERUSAHAAN - Ni Nyoman Ayu Suryandari; Ni Putu Lisa Ernawati; Ni Putu Yesa Idayani (Accounting Profession Journal (APAJI), 2025)
Audit quality is defined as the characteristics or description of audit practices and results according to the auditor's professional quality standards, where the auditor finds reports of material errors, mistakes, or omissions n the client's financial statements. This study aims to test and obtain empirical evidence regarding the effect of the Audit Committee, Audit Fees, KAP Rotation, Client Company Size, and Auditor Specialization on audit quality. Audit quality is proxied using a public accounting firm, which is measured by a dummy variable using the Big Four KAP and Non-Big Four KAP auditor groups. The population in this study were banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample determination used the purposive sampling method and obtained 31 samples with three years of observation so that the number of observations was 93 companies. The data analysis technique used was logistic regression analysis. The results of the study showed that the Audit Committee, Audit Fees, KAP Rotation, and Auditor Specialization did not have a significant effect on audit quality. This shows that the existence of an audit committee and high audit fees do not always guarantee quality, which is more dependent on auditor performance. In addition, KAP rotation does not guarantee effectiveness, considering that the adaptation process of new auditors takes time. However, Client Company Size has a positive and significant effect on audit quality, because large companies tend to have complexities that require more in-depth and high-quality audits. These results provide insight for companies in understanding the factors that affect audit quality.